SOCIAL WORK STUDENTS` EXPERIENCES IN â€œSELFâ€ AND PROFESSIONAL â€œSELFâ€ AWARENESS BY USING THE ART THERAPY METHOD - Bartkeviciene, Aiste (European Scientific Journal, ESJ, 2014)
This article analyzes social work students` experiences in â€œselfâ€ and professional â€œselfâ€ awareness by using the art therapy method. The article presents results from a qualitative research study involving six the first-year full-time social work students from university who practiced the art therapy method in the process of the studies. The research revealed the benefit of art therapy method for social work students at the level of personal â€œselfâ€ awareness and at the level of professional â€œselfâ€ awareness. The art therapy method is useful at the level of personal â€œselfâ€ awareness, since it allows social work students to recognize the strengths and weaknesses of personal â€œselfâ€. At the level of professional â€œselfâ€ awareness the art therapy method is useful in the process of social work studies, because it helps students to understand their professional identity, identify the benefit of acquired professional skills and professional skills that need to be improved through empathic, reflective and transformative learning experience.